2019
DOI: 10.1111/cas.13907
|View full text |Cite
|
Sign up to set email alerts
|

Significant antitumor effect of an antibody against TMEM180, a new colorectal cancer‐specific molecule

Abstract: The present state of therapy for colorectal cancer (CRC) is far from satisfactory, highlighting the need for new targets for this disease. We identified a new CRC‐specific molecule, TMEM180, a predicted 11‐pass transmembrane protein that apparently functions as a cation symporter. We developed an anti‐TMEM180 mAb and then succeeded in humanizing the mAb. Immunohistochemistry (IHC) in CRC with the mAb showed a similar positivity rate as compared with anti‐epidermal growth factor receptor mAb, and IHC with anti‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…Previously, we reported that TMEM180 is upregulated under low-oxygen conditions, and that TMEM180 may play an important role in the uptake or metabolism of glutamine and arginine in cancer cell proliferation [2]. We also showed that expression of TMEM180 is not essential for mouse development, as Tmem180-knockout mice do not exhibit embryonic, neonatal, or postnatal lethality [2].…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Previously, we reported that TMEM180 is upregulated under low-oxygen conditions, and that TMEM180 may play an important role in the uptake or metabolism of glutamine and arginine in cancer cell proliferation [2]. We also showed that expression of TMEM180 is not essential for mouse development, as Tmem180-knockout mice do not exhibit embryonic, neonatal, or postnatal lethality [2].…”
Section: Discussionmentioning
confidence: 80%
“…Previously, we reported that TMEM180 is upregulated under low-oxygen conditions, and that TMEM180 may play an important role in the uptake or metabolism of glutamine and arginine in cancer cell proliferation [2]. We also showed that expression of TMEM180 is not essential for mouse development, as Tmem180-knockout mice do not exhibit embryonic, neonatal, or postnatal lethality [2]. During the preparation of this manuscript, a group from Huazhong University of Science and Technology reported that SNP rs2001389 is significantly associated with pancreatic cancer risk, weakens the binding activity of the transcriptional repressor CCCTC-binding factor (CTCF), and is associated with the lower expression of MFSD13A/TMEM180.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations